2014
DOI: 10.5194/acpd-14-8015-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Air–sea fluxes of oxygenated volatile organic compounds across the Atlantic Ocean

Abstract: Abstract. We present air–sea fluxes of oxygenated volatile organics compounds (OVOCs) quantified by eddy covariance during the Atlantic Meridional Transect cruise in 2012. Measurements of acetone, acetaldehyde, and methanol were made in several different oceanic provinces and over a wide range of wind speeds of 1–18 m s−1. The ocean appears to be a sink for acetone in the higher latitudes of the North Atlantic but a source in the subtropics. In the South Atlantic, seawater acetone was near saturation relative … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(53 citation statements)
references
References 61 publications
6
47
0
Order By: Relevance
“…Our L4 surface data in October 2011 are, however, in agreement with measurements made at similar latitudes to L4, but in the North Atlantic, during October 2009 (Beale et al, 2013) and October 2012 (Yang et al, 2014). Acetone values similar to ours (Table 1) have also been reported in bulk seawater taken close to the Bahamas (Zhou and Mopper, 1997), perhaps indicative of lower acetone values in coastal and other high productivity regions.…”
Section: Surface Ovoc Data At L4supporting
confidence: 92%
See 2 more Smart Citations
“…Our L4 surface data in October 2011 are, however, in agreement with measurements made at similar latitudes to L4, but in the North Atlantic, during October 2009 (Beale et al, 2013) and October 2012 (Yang et al, 2014). Acetone values similar to ours (Table 1) have also been reported in bulk seawater taken close to the Bahamas (Zhou and Mopper, 1997), perhaps indicative of lower acetone values in coastal and other high productivity regions.…”
Section: Surface Ovoc Data At L4supporting
confidence: 92%
“…However, we observed no significant relationship throughout this L4 time series between methanol and chlorophyll a. Our observation of reduced methanol concentrations in 2012 compared to 2011 indicates there may be significant interannual variability in levels of this volatile, an observation supported by the difference in methanol concentrations reported from similar transects of the Atlantic Ocean in 2009 (Beale et al, 2013) and 2012 Yang et al (2013bYang et al ( , 2014 (Table 1).…”
Section: Surface Ovoc Data At L4supporting
confidence: 67%
See 1 more Smart Citation
“…To test the PCR primer sets as an assay for xoxF diversity in environmental habitats, water samples were collected in four coastal marine environments around the UK, including the Western Channel Observatory Station L4 (L4; salinity ∼35 g kg −1 , surface sample, water column depth ∼50 m); Stiffkey Salt Marsh (SM; salinity ∼30 g kg −1 , sample taken from the aqueous layer above sediment, high turbidity due to sediment resuspension); Cromer Beach (CB; surface sample, water column only a few meters deep) and offshore of Lowestoft (LO; bottom of a water column only a few meters deep). It has previously been shown that methanol concentrations in surface seawater at L4 ranged between 16–78 nM (Beale et al ., ) and across the Atlantic ocean between 15 nM and 361 nM (Beale et al ., ; Yang et al ., ). Algal growth and decay, atmospheric influx, precipitation and methane oxidation (most likely in sample SM) have been suggested as potential sources of methanol, but their contribution to the overall methanol budget still has to be elucidated (Felix et al ., ; Beale et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…An annual global sea to air flux of 34–57 Tg year −1 was calculated using an oceanic mixed‐layer photochemical flux model, with remotely sensed chromophoric dissolved organic matter (CDOM) absorption used as model input as a proxy to extrapolate rate data to the oligotrophic ocean (Millet et al, 2010; Wang et al, 2019). This modeled flux is substantially greater than the global sea‐to‐air acetaldehyde flux of ~3–17 Tg year −1 calculated based on in situ observations across the Atlantic Ocean (Beale et al, 2013; Yang et al, 2014). However, photochemical production of acetaldehyde in the oceans may not be sufficient to explain steady‐state concentrations of acetaldehyde in the surface mixed layer and therefore may not explain the observed sea‐to‐air flux, since biological production and consumption, and not photochemistry, may be the main factors affecting acetaldehyde concentrations in surface‐ocean waters (Zhu & Kieber, 2019).…”
Section: Introductionmentioning
confidence: 99%